The effect of social influence, trust, and entertainment value on social media use: Evidence from Pakistan - Muhammad Hasnain Abbas Naqvi; Yushi Jiang; Miao Miao; Mishal Hasnain Naqvi (Cogent Business & Management, 2020)
The rise of social networking sites (SNS) has changed our ways of communicating and conducting business all over the world. The present study explored the factors affecting the pervasive adoption of SNS by employing the use and gratification theory in considering their entertainment value, social influence, process of compliance, internalization, identification, and trust to investigate the sustainability of intentions to use SNS. This study also focused on the mediating effect of the relationship between trust and intentions to use SNS through users' attitudes which were significantly correlated with positive responses towards intention. Responses were gathered through a questionnaire survey, and PLS-SEM was used for the analysis of data. Seven out of eight hypotheses were supported and meaningful information was obtained in this study, which operators and designers can use as a guide for the development of sustainable SNS.
Keywords: 650; sustainable user generated content; social influence process; uses and gratification theory; online technologies; trust; Instagram; attitude; sustainable intention to use SNS; social media communication and interaction